2014
DOI: 10.2460/ajvr.75.6.602
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of anatomic landmarks for the placement of suture to achieve effective arytenoid cartilage abduction by means of unilateral cricoarytenoid lateralization in dogs

Abstract: Results indicated that placement of suture through the cricoid cartilage at the caudal border of the cricoarytenoid articulation was appropriate to sufficiently reduce LAR without increasing the risk of aspiration pneumonia through overabduction of the arytenoid cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
2
3
1
Order By: Relevance
“…This movement may have resulted in the relaxation of the tension suture between the thyroid cartilage and the muscular process of the arytenoid cartilage, thereby decreasing the rima glottidis area. In the authors' experience, limiting the decrease in the rima glottidis area by exerting more tension on the suture during TAL should be feasible, but the amount of tension required, and the subsequent results are beyond the scope of this study.In agreement with other studies, both techniques resulted in a notable increase in the rima glottidis area immediately after surgery 1,24,30,31 . Although the increase in the rima glottidis area was small in the TAL group at t1 ( P > .05), there were no postoperative abnormalities in any of the dogs, which confirmed that surgery was successful in the stabilization of the arytenoid cartilage.All owners reported decreased respiratory noise and increased exercise tolerance at t1, and the clinical examination showed that all dogs were in good condition.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This movement may have resulted in the relaxation of the tension suture between the thyroid cartilage and the muscular process of the arytenoid cartilage, thereby decreasing the rima glottidis area. In the authors' experience, limiting the decrease in the rima glottidis area by exerting more tension on the suture during TAL should be feasible, but the amount of tension required, and the subsequent results are beyond the scope of this study.In agreement with other studies, both techniques resulted in a notable increase in the rima glottidis area immediately after surgery 1,24,30,31 . Although the increase in the rima glottidis area was small in the TAL group at t1 ( P > .05), there were no postoperative abnormalities in any of the dogs, which confirmed that surgery was successful in the stabilization of the arytenoid cartilage.All owners reported decreased respiratory noise and increased exercise tolerance at t1, and the clinical examination showed that all dogs were in good condition.…”
Section: Discussionsupporting
confidence: 91%
“…Signalment, history, and the results of physical examination and laboratory testing were diagnostic of idiopathic laryngeal paralysis in all dogs 3,5,6,8,17 . Thyroid function tests and neurologic and radiographic examinations were unremarkable and in agreement with the findings of other studies 1,8,10 . A male predilection for this disorder has been reported but was not found in the present study 2,5,17 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Cadaveric airways have been utilized as models for canine laryngeal paralysis in several studies evaluating surgical effects on RGA and airway resistance 20–27 . The lack of muscle tone in the canine cadaver larynges causes passive adduction of both arytenoid cartilages, emulating a state of bilateral laryngeal paralysis.…”
Section: Discussionmentioning
confidence: 99%